Investigation on the cation location, structure and performances of rare earth-exchanged Y zeolite - 邱丽美 付颖 郑金玉 黄南贵 卢立军 高秀枝 忻睦迪 罗一斌 史延强 徐广通 (Journal of rare earths, 2017)
A series of Y zeolites exchanged with different amount of cerium and lanthanum cations were investigated. Comprehensive routine analysis tools including X-ray photoelectron spectroscopy（XPS）, X-ray fluorescence（XRF）, X-ray diffraction（XRD） and Py-Fourier transform infrared spectroscopy（Py-FTIR） were used to identify the cation location, and the result was verified via XRD Rietveld study. The results revealed that almost all the RE cations in RE-4, most cations in RE-8 to RE-14 and part of cations in RE-16 were located in the sodalite cage. The Al~（IV）/（Al~V＋Al~（VI）） values revealed by ~（27）Al MAS NMR spectra, the silicon aluminum ratio of the framework（SARF） values deduced from ~（29）Si MAS NMR spectra and XRD, and hydroxyl amount were reasonably in accordance with the location and content of rare earth cations. The hydrothermal stability derived from in situ XRD investigation and catalyst activity provided by micro-activity test manifested that samples RE-8 to RE-14 exhibited better performances than RE-4 and RE-16, among which RE-12 had the best properties. The phenomena were interpreted by the cation location and structural properties.